Evaluation of Some Platelet Parameters in a Group of Elderly People - Sie, P; Montagut, J; Blanc, M; Boneu, B; Caranobe, C; Cazard, J C; Biermé, R (Thrombosis and Haemostasis, 1981)
Platelet production time (PPT), plasmatic β-thromboglobulin (β-TG), platelet density distribution, and mepacrine labelled granular content of the platelets were simultaneously determined in a group of elderly subjects. Vascular deterioration, assessed by the history and clinical examination, was variable in extension and severity. PPT was slightly but not significantly shortened, whereas the raised β-TG level and diminished platelet density and granular content suggested an in vivo release reaction process. The results are not correlated with the apparent severity of vascular deterioration, and the release reaction may not be solely related to enhanced platelet-vessel wall interactions.
Keywords: Platelets; Elderly people